2014
DOI: 10.1155/2014/281790
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Early Inflammatory Response and Clinical Evolution of the Severe Multiorgan Failure in Mechanical Circulatory Support-Treated Patients

Abstract: Background. The mechanical circulatory support (MCS) is an effective treatment in critically ill patients with end-stage heart failure (ESHF) that, however, may cause a severe multiorgan failure syndrome (MOFS) in these subjects. The impact of altered inflammatory response, associated to MOFS, on clinical evolution of MCS postimplantation patients has not been yet clarified. Methods. Circulating cytokines, adhesion molecules, and a marker of monocyte activation (neopterin) were determined in 53 MCS-treated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…As a single center study, we are able to include patients receiving similar medical care with similar waiting time for transplantation. In addition, our work confirms previous studies that have also identified IL-6, IL-8, TNF-a, and MDC as associated with heart failure and MCSD implantation [6,29,32,33]. Future multicenter studies will be important to validate our pilot findings and evaluate whether pre-implant as well as post-implant assessment is associated with clinical outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a single center study, we are able to include patients receiving similar medical care with similar waiting time for transplantation. In addition, our work confirms previous studies that have also identified IL-6, IL-8, TNF-a, and MDC as associated with heart failure and MCSD implantation [6,29,32,33]. Future multicenter studies will be important to validate our pilot findings and evaluate whether pre-implant as well as post-implant assessment is associated with clinical outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Inflammation is know to play a role in adverse outcomes in older patients, however, less is known about the role of pro-inflammatory monocytes and cytokines in the setting of MCSD implantation. Previously assessed markers such as C-reactive protein and procalcitonin have not added significantly to prediction of adverse outcomes after MCSD, suggesting the need for more immunologically oriented assessment [29,30]. In this analysis of MCSD recipients, we found that despite similar etiologies of heart failure and types of interventions, older patients demonstrated increased frequency of the pro-inflammatory CD14++/CD16− classical monocyte.…”
Section: Discussionmentioning
confidence: 73%
“…2–5 Predictors for risk of infection in LVAD recipients have been sought but to date remain unreliable. 6,7…”
mentioning
confidence: 99%
“…Given that, we hypothesized that an increase in plasma OSM levels could serve as a more sensitive predictor of infection risk than previously proposed biomarkers. 6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation